The U.S. and the UK in the United Nations: The Impact of the Special Relationship (2001 – 2017) - A. O. Mamedova (Vestnik MGIMO-Universiteta)
Currently U.S.-UK cooperation in the UN does no attract as much attention as it deserves. Despite a conspicuous disparity in the countries’ military and economic might, they have maintained close ties for more than seventy years, which inevitably affects their position in the UN. The allies’ role in the 2003 invasion of Iraq cast suspicion on their activities in the organization. In the early 21st century, the UN itself was faced with a number of challenges, such as terrorism and regional conflicts; U.S. frustration with its effectiveness led to some reform efforts.Covering the years 2001 – 2017, the article consists of three parts. The first part focuses on quantitative and qualitative parameters determining the U.S.’s and the UK’s roles in the UN and compares their approaches to it. The second part discusses the activity of American and British permanent representatives to the UN, based on their memoirs and interviews. The third part analyses some examples of cooperation and competition in the UN. The list of examples is illustrative rather than comprehensive given the existence of the special relationship.The analysis of U.S.-UK cooperation in the UN reveals its ambiguous nature, but it does not serve to debunk the myth of the special relationship. The cooperation is largely pragmatic.